COMPARATIVE ANALYSIS OF PARAMETERS OF A COMPOSITE COIL FOR MAGNETIC PULSE MATERIAL WORKING - E.I. Baida (National Technical University "Kharkiv Polytechnic Institute", 2013)
The article presents evaluation of parameters of a two-layer coil consisting of a thin outer layer and a conductive solid substrate as compared with parameters of a solid inductor.